Implementasi Pembelajaran Berdiferensiasi dengan Model PjBL untuk Meningkatkan Kemampuan Kolaborasi dan Hasil Belajar Siswa SD - Nurhidayati, Hesti; Oktavia, Anggita; Hadiyanti, Agnes Herlina Dwi (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This research aims to improve the collaboration skills and learning outcomes of fifth grade students at Kanisius Elementary School, Kotabaru. The type of research used is Classroom Action Research, including planning, action, observation and reflection. The subjects of this research were fifth grade students at Kanisius Elementary School, Kotabaru. The data collection techniques used are documentation and observation. Data collection instruments include implementation documentation, student learning outcomes and collaboration skills observation sheets. The research results showed an increase in the average student learning outcomes with results of 68.75 in cycle I and 75.75 in cycle II. The increase in average results occurred in students' collaboration skills. Cycle I showed a result of 69.07%, while cycle II showed a result of 78.22%. This proves that differentiated learning using the PjBL learning model can improve the learning outcomes and collaboration skills of class V students at SD Kanisius Kotabaru. With this research, teachers are expected to improve Indonesian language learning outcomes and students' collaboration abilities by considering learning models based on the needs of each student.